BATAS MEDAN LEMAH PADA GRAVITASI f(T) - Tika Restianingsih (Universitas Riau, 2022)
We derive the field equation of f(T) gravity at the weak field limit obtained by teleparallel Lagrange action of a function of torsion scalar T. The weak field limit in teleparallel gravity is to assume that tetrad experiences small perturbation and ignore the higher order. Tetrad perturbation is equivalent to metric perturbation in general relativity and can be transformed into one another. If we take the special case f(T) = T then the equation will be equivalent to the gravitational field equation obtained by the Einstein-Hilbert action. The equation of fields is simplified using the trace reversed method for metric perturbation and Lorentz gauge condition. The final equation has the form of the wave equation with an additional derivative of function f(T). Technically, this equation is the gravitational waves equation in terms of f(T) gravity. In a vacuum with zero energy and momentum tensor, the field equation reduces to the gravitational waves equation in a vacuum.